Performance Review of Housekeeping Room Attendant in Hotel Puri Garden Semarang - Thoriq, Naufal; Intiar, Septa; Jabbar, Umar Abdul; Maryani, Tri; Aryaningtyas, Aurilia Triani; Risyanti, Yustina Denik (PT. Hafasy Dwi Nawasena, 2024)
This study assesses the efficiency and effectiveness of the room attendants working in the housekeeping department at Hotel Puri Garden Semarang. The cleaning department plays a crucial role in upholding the cleanliness standards of the hotel and has a substantial impact on client satisfaction and the hotel's reputation. The study examines the elements that influence the performance of room attendants, with a particular focus on the impact of technological improvements, environmentally friendly practices, and staff well-being. Data were gathered using a qualitative descriptive approach, employing interviews, questionnaires, documentation, and direct observation. The results emphasise the significance of directly observing, obtaining feedback from guests, conducting frequent performance evaluations, and utilising staff surveys to evaluate and enhance the performance of room attendants. Analysis of performance data uncovers trends that suggest operational inefficiencies and shortcomings in training. The study emphasises the importance of thorough performance assessments in order to identify areas for development and conduct focused training interventions. Suggested areas for further research encompass investigating the enduring effects of adopted improvement methods, examining the correlation between staff happiness and performance outcomes, and analysing the role of technology in optimising housekeeping operations. The study asserts that adopting a multidimensional strategy is crucial in improving the efficiency and effectiveness of room attendants, which in turn results in increased visitor satisfaction and improved hotel performance.